Conservation and Dispersion of Genes Conferring Resistance to Tomato Begomoviruses between Tomato and Pepper Genomes - Mangal, Manisha; Srivastava, Arpita; Sharma, Rita; Kalia, Pritam (Frontiers in Plant Science, 2017)
In the present climate change scenario, controlling plant disease through exploitation of host plant resistance could contribute towards the sustainable crop production and global food security. In this respect, the identification of new sources of resistance and utilization of genetic diversity within the species may help in the generation of cultivars with improved disease resistance. Begomoviruses namely, Tomato yellow leaf curl virus (TYLCV) and Chilli leaf curl virus (ChLCV) are known to cause major yield losses in several economically important crop plants of the family Solanaceae. Though co-occurrence, association and synergistic interactions among these viruses in the host plants is reported, whether orthologous genetic loci in related host plants could be responsible for conferring resistance to these viruses has not been investigated yet. Several loci including Ty1, Ty2, Ty3, Ty4 and ty5 have been reported to confer resistance to leaf curl viruses in tomato. Here, we examined the pepper orthologous markers, corresponding to these QTL regions, for polymorphism between ChLCV susceptible and resistant genotypes of pepper. Further, to examine if the polymorphic markers are segregating with the disease resistance, Bulk Segregant Analysis (BSA) was performed on F2 population derived from crosses between resistant and susceptible lines. However, none of the markers showed polymorphism in BSA suggesting that the tested markers are not linked to genes/QTLs responsible for conferring resistance to ChLCV in the selected genotypes. In silico analysis was performed to study the synteny and collinearity of genes located within these QTL regions in tomato and pepper genomes, which revealed that more than 60% genes located in Ty2 and Ty4, 13.71% genes in Ty1, 23.07% in Ty3, and 44.77% genes located within ty5 QTL region in tomato are conserved in pepper genome. However, despite such a high conservation in gene content, the linkage relationship in these regions seems to be greatly affected by gross rearrangements in both the species.